The Place of Crimes against Humanity under the Ethiopian Legal System: A Reflection - Asgedom, Messay (Bahir Dar University Journal of Law, 2022)
Crimes against humanity are among the most heinous forms ofinternational crimes that shock the conscience of mankind. The internationalcommunity has sporadically prosecuted perpetrators of these crimes since theaftermath of World War II and then after. Apart from internationalprosecutions, different countries have enacted laws that penalize thecommission of such crimes. Some others have applied customaryinternational law to prosecute perpetrators of these crimes. Some years back,Ethiopia has prosecuted former Derg officials for their alleged commission ofcrimes against humanity. This author intends to explore the place of crimesagainst humanity under the Ethiopian legal system. The paper begins with theexposition of the concept of crimes against humanity and its constitutiveelements under customary international law. It then proceeds to specificallyexplore the place of crimes against humanity under the Ethiopian legalsystem. Finally the paper draws a conclusion.